DOMESTIKASI IKAN ENDEMIK DANAU LINDU Xenopoecilus sarasinorum DENGAN PEMBERIAN JENIS PAKAN BERBEDA - Wilkerson, Azis (AgriSains, 2012)
Xenopoecilus sarasinorum is an endemic fish from Lake Lindu; its existence is not widely known. The fish is listed as an endangered fish according to IUCN 1996. One of efforts to conserve the fish is domestication. This study was asmed to determine the growth of X. sarasinorum domesticated with different types of feed. The research was conducted from December 2012 until February 2013 in the Laboratory of Aquaculture, Faculty of Animal Husbandry and Fisheries, Tadulako University Palu. This study used a completely randomized design consisting of three treatments i.e. treatment A (silk worms feeding), treatment B (mosquito larvae feeding), treatment C (blood worms feeding) and six experimental replicates so that there were 18 experimental units. The results showed that the best feed for X. sarasinorum growth was silk worms. The absolute weight gained by the fish wich given silk worms wasÂ  0,330 g. Based on the results of analysis of variance (ANOVA) provision of different types of feed that gives a very real effect on the growth of fish biomass X. sarasinorum (P <0,01). Key words : Domestication, endemic fish, Lake Lindu, Xenopoecilus sarasinorum.